Analisis Tugas Pokok Pembimbingan Klien Pemasyarakatan (BAPAS) dalam Mewujudkan Reintegrasi Sosial - Riyadi Riyadi (Syntax Corporation Indonesia, 2023)
Guidance is a series of law enforcement in the community which is carried out through efforts to restore the unity of life and livelihood relationships of correctional clients so that they can realize their mistakes, improve themselves and not repeat criminal acts and can be accepted back by the community. This article uses a qualitative literature research approach, in which researchers test theories by analyzing data sources derived from literature studies. The results showed that the guidance of correctional clients is carried out by improving the quality, devotion to God Almighty, intellectual, attitudes and behavior, professional, physical and spiritual health of correctional clients. The role of the Correctional Center in particular is to provide guidance to Correctional clients as stipulated in Government Regulation Number 31 of 1999 concerning Guidance and Guidance of Prisoners. To realize Social Integration, it is necessary to analyze the main tasks comprehensively about the main responsibility of guiding correctional clients.